PANCASILA SEBAGAI IDEOLOGI NEGARA DAN HAK ASASI MANUSIA DALAM MENJAGA KEUTUHAN NEGARA KESATUAN REPUBLIK INDONESIA - Luh Suryatni (JURNAL ILMIAH HUKUM DIRGANTARA, 2014)
Ideology in our life as a State can be interpreted as the majority consensus of citizens about the basic values that they want to realize by establishing a State. In this case, it is often also referred to as philosophische grondslag or weltanschauung, which is the deepest thought and desire of its citizens to establish a state. Ideology and personality of the Indonesia as a crystallization of the sacred values of Indonesia as a nation, puts human in the lofty dignity as a sentient that believe God Almighty with the awareness of carrying out his nature as being personal and social beings. As enshrined in the preamble to the Constitution of 1945, where the Unitary State of the Republic of Indonesia (NKRI) respects any attempt of a nation for outlining and regulating human rights in accordance with the system of values and ideology of each. In this case, Indonesia as a nation will uphold and enforce human rights that corresponding to the Pancasila as the State ideology as to remain firmly hold as Unitary State of the Republic of Indonesia Keywords : Ideology, Pancasila, Human Rights, State